Determinants for Meaningful Clinical Improvement of Pain and Health‐Related Quality of Life After Spinal Cord Stimulation for Chronic Intractable Pain. Issue 3 (10th December 2018) - Campos, Wuilker Knoner; Linhares, Marcelo Neves; Sarda, Jamir; Santos, Adair Roberto Soares; Licinio, Júlio; Quevedo, João; Lin, Kátia; Walz, Roger
Abstract : Objectives: Previous studies demonstrated significant improvement in mean pain scores and quality of life (QOL) scales in patients with chronic pain who underwent spinal cord stimulation (SCS). However, the number of individuals who experience relevant improvements in QOL, termed the meaningful clinical improvement (MCI), is not known. The present study investigated changes in pain measurements based on MCI after SCS. Materials and Methods: Thirty‐four patients with chronic intractable pain completed scales of pain (visual analogue scale [VAS]), QOL (SF‐36), and psychological dimensions during a 22‐month follow‐up period (mean). Patient‐centered MCI of the VAS and SF‐36 domain scores were determined based on the MacNab criteria of surgical global effectiveness. Independent presurgical predictors for MCI in the VAS and SF‐36 domains were analyzed using multiple binary logistic regression. Results: There was significant improvement of pain and QOL after the SCS ( p < 0.00001). Twenty‐three patients (67.6%) reached an MCI of pain, and 16 (47.7%)–23 (67.7%) reported an MCI of QOL. Predictors of MCI included ≥80% paresthesia coverage of the painful area, lower levels of anxiety and catastrophizing symptoms, shorter pain duration, female gender and no use of opioids before surgery. MCI of pain and QOL was observed in 50%–70% of patients with chronic pain after SCS. Conclusions: The identification of determinants for MCI is a challenge to improve the accuracy of prognostic models in SCS for patients with chronic pain. Our results, if confirmed in other populations with a larger sample size, have implications for patients with chronic pain who are candidates for SCS treatment.